Athlete assessments in orienteering: Differences in physiological variables between field and laboratory settings - Rattray, B.; Roberts, A. D. (European Journal of Sport Science, 2012)
Orienteers have been physiologically assessed in the past using treadmill protocols designed for road and track runners, neglecting the specific conditions in which they compete. The purpose of the present study was to quantify the agreement between physiological data obtained from a specific field-based protocol with that obtained with a matched laboratory-based assessment. Ten elite orienteers completed a six-stage incremental test in both field and laboratory settings. The field test comprised a marked 803-m course over flat forest terrain, with the participants paced by a bicycle parallel to the course. The laboratory test was conducted on a treadmill at a 4.5% grade. Oxygen consumption VO2 and heart rate were measured continuously and blood lactate concentration at the completion of each stage. Regression statistics and an analysis of variance were used to analyse the data. Heart rate, blood lactate concentration, and VO2 increased significantly with increases in running speed, but there were no significant differences in heart rate, blood lactate concentration or VO2 between the field and laboratory tests at any running speed. Regression statistics revealed that only trivial or small differences existed for measures associated with submaximal testing, including speed at the onset of blood lactate accumulation. There was less agreement for maximal data with differences typically small to moderate. In general, there were only minimal differences between the field and laboratory tests, supporting their use in this population. This initial study provides the first steps in the creation of improved test protocols for terrain running based performance.